Local Safety Concerns of Repited Dexamethasone Intravitreal Implant (Ozurdex®) For Macular Diseases - Gallego-Pinazo, Roberto; Hernández-Martinez, Pablo q; Hervás-Ontiveros, Ana; Martínez-Castillo, Sebastián; Dolz-Marco, Rosa; Arévalo, J. Fernando; Wu, Lihteh; Díaz-Llopis, Manuel (Journal of Ocular Diseases and Therapeutics, 2013)
Introduction: The objective of the present study was to analyze the expanding indications for the dexamethasone intravitreal implant (Ozurdex®) in macular edema of varied diseases, and determine its safety concerns. Materials and Methods: We retrospectively reviewed the ophthalmic charts of patients treated with at least one intravitreal injection of Ozurdex® since April 2010 to October 2011. Data regarding complications of the procedure as well as the need for cataract surgery were collected. No patient with the diagnosis of glaucoma was included in the present study. Early recurrences where treated with laser photocoagulation or intravitreal ranibizumab at the discretion of the physician; late recurrences where treated with a new Ozurdex® injection. Results: The causative diseases of ME in the 214 eyes of our sample were: diabetic macular edema (101 eyes of 84 patients); branch retinal vein occlusion (27 eyes of 27 patients with superior temporal branch occlusion; 6 eyes of 6 patients with inferior temporal branch occlusion); central retinal vein occlusion (23 eyes of 23 patients); uveitic macular edema (13 eyes of 11 patients). Patients with other indications such as exudative age-related macular degeneration (27 eyes of 27 patients), and pseudophakic cystoid macular edema (7 eyes of 7 patients). Regarding complications, we found a rate of posterior cataract progression in 69.6% of phakic eyes after receiving a second intravitreal Ozurdex® for the treatment of ME. A significant IOP increase was evidenced in 21.18% of cases following the first Ozurdex® implant. Patients with uveitic macular edema (UME) showed the greatest rate of IOP increase (53.86%) following Ozurdex® implant. In addition, anterior chamber migration of the Ozurdex® implant was seen in 2 cases with lens posterior capsule rupture. Discussion: This is a descriptive study of 214 eyes of 189 patients treated with intravitreal Ozurdex® in real-life conditions, which adds an important value for the retinal physicians. Further long-term studies are warranted in order to establish a more accurate safety profile of Ozurdex® for retinal diseases.